2011
DOI: 10.1186/1475-2859-10-23
|View full text |Cite
|
Sign up to set email alerts
|

Single cell analysis applied to antibody fragment production with Bacillus megaterium: development of advanced physiology and bioprocess state estimation tools

Abstract: BackgroundSingle cell analysis for bioprocess monitoring is an important tool to gain deeper insights into particular cell behavior and population dynamics of production processes and can be very useful for discrimination of the real bottleneck between product biosynthesis and secretion, respectively.ResultsHere different dyes for viability estimation considering membrane potential (DiOC2(3), DiBAC4(3), DiOC6(3)) and cell integrity (DiBAC4(3)/PI, Syto9/PI) were successfully evaluated for Bacillus megaterium ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…In this case, the protein of interest can be tagged by immunofluorescence staining directly at the cell surface and easily detected by FC. David et al [67] used FC for analyzing cell viability and secretory capacity for the production of antibody fragment by Bacillus megaterium. Protein secretion was followed by staining the products attached to the cells when exported by membrane-coupled secretory (Sec) pathway.…”
Section: Production Of Metabolites and Recombinant Systems: Robustnesmentioning
confidence: 99%
“…In this case, the protein of interest can be tagged by immunofluorescence staining directly at the cell surface and easily detected by FC. David et al [67] used FC for analyzing cell viability and secretory capacity for the production of antibody fragment by Bacillus megaterium. Protein secretion was followed by staining the products attached to the cells when exported by membrane-coupled secretory (Sec) pathway.…”
Section: Production Of Metabolites and Recombinant Systems: Robustnesmentioning
confidence: 99%
“…This may be caused by PI entry mediated by cell wall perforation encountered during cell division and cell wall synthesis (15,47), especially for exponentially growing cells. Concomitantly, the frequency of damaged S. aureus cells increased.…”
Section: Viability During Growth In Pure and Mixed Culturementioning
confidence: 99%
“…Concomitantly, the frequency of damaged S. aureus cells increased. This may be caused by PI entry mediated by cell wall perforation encountered during cell division and cell wall synthesis (15,47), especially for exponentially growing cells. Accordingly, PI uptake in highly reproductive bacteria during exponential growth was reported in several studies (47,48).…”
Section: Viability During Growth In Pure and Mixed Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that even simple parameters as the cell size, granularity or DNA content give already valuable insights into the metabolic status and the fitness of the whole population (Erlebach et al ., ; Hewitt and Nebe‐von‐Caron, ; Müller, ). Membrane potential (MP) and integrity are further parameters, which can be analysed by the use of specific fluorescent dyes and do provide important information regarding the cellular stress response and viability parameters, which were shown in several studies to significantly correlate with productivity and economic efficiency of the bioprocess (Hewitt et al ., ; David et al ., ). When equipped with a cell sorting capability for separation of single bacterial cells, FC analyses can be complemented with further downstream investigations, such as microscopy, cultivation in liquid or on agar plates, or even Omics ‐based technologies (Bernas et al ., ; Wiacek et al ., ; Jehmlich et al ., ).…”
Section: Introductionmentioning
confidence: 99%